"More like a support tool": Ambivalences around digital health from medical developers' perspective. Issue 1 (March 2021) - Lenz, Sarah
Against the background of the increasing importance of digitization in health care, the paper examines how medical practitioners who are involved in the development of digital health technologies legitimate and criticize the implementation and use of digital health technologies. Adopting an institutional logics perspective, the study is based on qualitative interviews with persons working at the interface of medicine and digital technologies development in Switzerland. The findings indicate that the developers believe that digital health technologies could harmonize current conflicts between an increasing economization of the health care system and professional–ethical demands. At the same time, however, they show that digital technologies can undermine the demand for medical autonomy, a central element of the medical ethos.